Enhanced Potency of a Broad H7N9-Neutralizing Antibody HNIgGA6 Through Structure-Based Design - Chen, Cong; Liu, Zuliang; Liu, Liguo; Wang, Jianmin; Jin, Qi (Frontiers in Microbiology, 2020)
H7N9 influenza virus was first isolated in 2013 and has caused five epidemic waves among humans to date. Treatment opinions are currently limited. Previously, we characterized a human neutralizing antibody, HNIgGA6, by isolating rearranged heavy-and light-chain genes from convalescent patients. The mAb disrupts viral attachment to the cellular receptor by directly interposing into the receptor binding site (RBS) and broadly neutralizing divergent H7N9 strains. To increase the protective efficacy of HNIgGA6, we employed a structure-based design to enhance its binding affinity and neutralization potency. When the serine at position 28 on light-chain complementarity-determining region 1 (LCDR1) was substituted by a histidine, compared to HNIgGA6, the mutated antibody showed an approximately 3-fold increase in HA-binding affinity and 10-fold enhancement in neutralization potency in vitro. Importantly, the S28H variant also exhibited broad H7N9-neutralizing activity. When administered to BALB/c mice, mAb S28H showed enhanced potency in inhibiting the pulmonary virus titre and reducing lung lesions and resulted in better protection of the animals than did the original antibody.